The Design and Implementation of Fan Chips as Cooling for Milling Process on Aluminum Alloy 5086 to Increase Tool Life - Agus Sifa; Dedi Suwandi; Tito Endramawan; Alam Aulia Rachman (Bandung State Polytechnic (Politeknik Negeri Bandung), 2021)
In the metal machining process, especially in the milling process, the parameters that affect the quality milling process results are cooling media because it affects the tool life used. This paper aims to determine the performance of using fan chips as the coolant in the dry milling process area. The method used is the computational fluid dynamic (CFD) method and the experimental milling process on a workpiece made from aluminum alloy 5086. In experimental testing using a variation of the milling machine spindle rotation. The simulation test results on the fluid flow character on fan chips with a protector producing a central character with a small area. In contrast, fan chips without a protector make a central character with a broader area. The wind speed data in simulation testing and experimental testing produced the same trend graph. The results of the performance of fan chips after experimented with variations in spindle rotation, cooling process on area occurs when the motor spindle rotates above 1120 Rpm on the fan chips with a protector, and the engine spindle rotates above 770 Rpm on the fan chips without a protector. The effect of fan chips on tool life affects increasing tool life by 8 minutes on installing fan chips with a protector and increasing tool life by 12 minutes on installing fan chips without a protector.